Asymmetric synthesis of beta-fluoroaryl-beta-amino acids - Davies, S; Fletcher, A; Lv, L; Roberts, P; Thomson, J (2012)
The conjugate addition of lithium (R)-N-benzyl-N-(α-methylbenzyl) amide to a range of β-fluoroaryl-α,β-unsaturated esters gave the corresponding β-amino esters with high diastereoselectivity and in good isolated yields. Sequential treatment of the resultant β-fluoroaryl-β- amino esters under optimised hydrogenolysis conditions, followed by ester hydrolysis with 2.0 M aq HCl, provided access to a range of β-fluoroaryl- β-amino acids in good yield. © 2012 Elsevier Ltd. All rights reserved.